Perbandingan Pengungkapan Identitas Etika Islam pada Perbankan Syariah Indonesia: Studi pada Periode 2014-2018 - Muhammad, Rifqi; Puspitasari, Dianita Nur Anggraeni; Asmirawati, Asmirawati (Akuntansi: Jurnal Akuntansi Integratif, 2022)
The study aims to analyze the disclosure of Islamic ethical identity of full-fledge Islamic banks (BUS) and Islamic windows (UUS). This study also compares the full-fledge Islamic banks (BUS) and Islamic windows (UUS) which are better between the two groups. This study uses a sample of 12 BUS and 16 UUS in the period of 2014-2018. The sampling selection uses purposive sampling. This study examines the index of Islamic ethical identity disclosure using the Ethical Identity Index (EII). The results of this study indicate that full fledge Islamic banks (BUS) and Islamic windows (UUS) are no significant differences in the disclosure of. This study also discusses the disclosure on each dimension of EII.